Site-level restoration strategies for degraded primary forest - Sabogal, C. (ITTO, 2005)
This chapter sets out the site-level strategies and their associated silvicultural techniques for restoring degraded primary forest, managing secondary forest and rehabilitating degraded forest land within the context of an forest landscape restoration (FLR) program. It is intended to provide an overview of the different strategies and methods, along with basic practical information on their use and guidance as to which methods are most appropriate in different situations. References are provided to point readers to more detailed technical guidelines. Table 9.1 summarizes the restoration objectives and methods most suited for different types of degraded forest and other lands. This chapter outlines the main strategies and silvicultural options available for the restoration of degraded primary forests, with particular emphasis on tropical rainforests. It provides some basic advice on how to choose the most appropriate methods and suggests further reading for more detailed practical guidance on undertaking the different techniques.